2009
DOI: 10.1002/anie.200804714
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Fluoroionophore Based on BODIPY‐functionalized Magnetic Silica Nanoparticles: Removal of Pb2+ from Human Blood

Abstract: Get the lead out: The title fluorescence receptor exhibits a high affinity and selectivity for Pb(2+) over competing metal ions in water (see picture) with an overall emission change of approximately 8-fold at the emission maximum for Pb(2+). The fluorescence receptor can remove 96 % of 100 ppb Pb(2+) from human blood, and can be useful and effective for the selective and rapid removal of Pb(2+) in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…On the other hand, removal of toxic metals from contaminated water is necessary to remedy the heavy metal pollutions. Nowadays, some techniques have been developed to separate toxic metals from various samples, such as, redox co-precipitation, chemical deposition, ion displacement, membrane filtering, absorption technique and solid-phase extraction [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, removal of toxic metals from contaminated water is necessary to remedy the heavy metal pollutions. Nowadays, some techniques have been developed to separate toxic metals from various samples, such as, redox co-precipitation, chemical deposition, ion displacement, membrane filtering, absorption technique and solid-phase extraction [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, this research group fabricated a highly sensitive and selective GO-based fluorescent sensor, 17 which realized label-free Hg 2+ ions detection for the first time. Additionally, Jung et al reported a series of nanomaterials for detecting and removing toxic metal ions, which can recognize target ions with high degrees of selectivity among heavy metal ions in aqueous solution, including acyclic receptor immobilized MS, 18 BODIPY-functionalized MSN 19 and so on. 20−23 Usually, there is more than one type of ions in pollutant, and thus the ability to detect and remove multiple ions is critical for many practical applications, such as environmental renovation, toxin monitoring, and groundwater analysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Boron complexes, mainly boron dipyrromethene (BODIPY) dyes [6][7][8][9] are the most important types of fluorescent dyes due to their outstanding optical properties such as, high fluorescence quantum yields, extinction coefficients, sharp absorption and fluorescence emission spectra. BODIPY dyes are extensively used as a chemosensors [10][11][12][13][14][15][16], in the biolabeling [17,18], in dye-sensitized solar cells [19,20] and photodynamic therapy [21,22]. However, their use as an electroluminescent material is restricted due to their small stokes shifts which leads to self-quenching [23,24].…”
Section: Introductionmentioning
confidence: 99%